2017
DOI: 10.1016/j.biomaterials.2017.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic tweezing cytometry enhances osteogenesis of human mesenchymal stem cells through cytoskeletal contractility and YAP activation

Abstract: Human mesenchymal stem cells (hMSCs) have great potential for cell-based therapies for treating degenerative bone diseases. It is known that mechanical cues in the cell microenvironment play an important role in regulating osteogenic (bone) differentiation of hMSCs. However, mechanoregulation of lineage commitment of hMSCs in conventional two-dimensional (2D) monocultures or bioengineered three-dimensional (3D) tissue constructs remains suboptimal due to complex biomaterial design criteria for hMSC culture. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 35 publications
6
44
1
Order By: Relevance
“…Our results are consistent with Dalby, Furukawa and Fu's study, which demonstrate that osteogenesis is mediated by enhanced focal adhesion, 28 actin polymerization 25 and YAP activation. 64 A schematic representation of the mechanistic phenome at play is illustrated in Fig. 10 and describes the effect of similar C AR , stimulated by different wrinkle dimensions, on the osteogenic differentiation, which is at least partly mediated by the mechanical properties of hBM-MSCs and possibly connected to the focal adhesions providing the contact guidance information and YAP signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with Dalby, Furukawa and Fu's study, which demonstrate that osteogenesis is mediated by enhanced focal adhesion, 28 actin polymerization 25 and YAP activation. 64 A schematic representation of the mechanistic phenome at play is illustrated in Fig. 10 and describes the effect of similar C AR , stimulated by different wrinkle dimensions, on the osteogenic differentiation, which is at least partly mediated by the mechanical properties of hBM-MSCs and possibly connected to the focal adhesions providing the contact guidance information and YAP signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the importance of YAP signaling in mediating transcriptional activity from upstream mechanosensitive human Mesenchymal Stem Cell (hMSC) osteogenesis ( Xue et al, 2017 ). Nonetheless, it also indicated that YAP/TAZ has the ability to link cell mechanics to Notch signaling in controlling epidermal stem cell fate and peripheral myelination ( Poitelon et al, 2016 ; Totaro et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contractile force measurements were performed as described before 35 . Briefly, hESCs were seeded on PDMS micropost array (PMA) either as single cells or colonies, and incubated overnight to allow attachment.…”
Section: Methodsmentioning
confidence: 99%